Identifikasi Spatial Pattern dan Spatial Autocorrelation pada Indeks Pembangunan Manusia Provinsi Papua Barat Tahun 2012 - Eva Khoirun Nisa (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2017)
One of the support aspect the country development is human resource quality. When we talking about human resource quality, it’s not separated with human development. The international standard of human development is Human Development Index (HDI). HDI becomes important indicator in West Papua province which is one of the youngest provinces in Papua. There is spatial effect of human development condition among districts in West Papua. Spatial Pattern and Spatial Autocorrelation as statistical methods can be used to identify HDI dependency among districts in West Papua. The statistical tests on Spatial Autocorrelation has found that there was no spatial independency of HDI on 2017 among districts in West Papua province.================================================== Salah satu aspek yang mendukung pembangunan suatu negara adalah kualitas sumber daya manusia. Berbicara mengenai kualitas sumber daya manusia maka tidak lepas dengan pembangunan manusia. Ukuran standar pembangunan manusia yang dapat digunakan secara internasional yaitu Indeks Pembangunan Manusia (IPM) atau Human Development Index (HDI). IPM menjadi hal yang penting bagi Provinsi Papua Barat mengingat Papua Barat menjadi salah satu provinsi termuda hasil pemekaran wilayah Provinsi Papua. Sangat dimungkinkan adanya pengaruh spasial pada kondisi pembangunan manusia antar kabupaten/kota di Provinsi Papua Barat. Spatial Pattern dan Spatial Autocorrelation menjadi metode statistika yang dapat mengidentifikasi adanya dependensi IPM antar kabupaten/kota di Provinsi Papua Barat. Dengan beberapa pengujian statistik Spatial Autocorrelation menghasilkan bahwa tidak terdapat dependensi spasial terhadap angka IPM pada tahun 2012 antar kabupaten/kota di Provinsi Papua Barat.